2020
DOI: 10.1111/exd.14130
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation in male androgenetic alopecia—Sex hormones and beyond: Evidence from recent genetic studies

Abstract: Male-pattern hair loss, also termed androgenetic alopecia (AGA), is a highly prevalent age-related condition that is characterized by a distinct pattern of hair loss from the frontotemporal and vertex regions of the scalp. The phenotype is highly heritable and hormone dependent, with androgens being the recognized critical hormonal factor. Numerous molecular genetic studies have focused on genetic variation in and around the gene that encodes the androgen receptor. More recently, however, the availability of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 114 publications
(185 reference statements)
2
15
0
4
Order By: Relevance
“…Its central etiopathogenic feature is an increased sensitivity of the follicle to dihydrotestosterone; however, both inflammatory and environmental factors have contributed. 82 In the last 20 years, several studies have shown a correlation between MAG and CVR. 83 Early on, small case-control studies showed a higher prevalence of traditional and non-traditional CVR factors like obesity, diabetes, low HDL cholesterol, and cIMT.…”
Section: Other Emergent Cvd-associated Skin Diseasesmentioning
confidence: 99%
“…Its central etiopathogenic feature is an increased sensitivity of the follicle to dihydrotestosterone; however, both inflammatory and environmental factors have contributed. 82 In the last 20 years, several studies have shown a correlation between MAG and CVR. 83 Early on, small case-control studies showed a higher prevalence of traditional and non-traditional CVR factors like obesity, diabetes, low HDL cholesterol, and cIMT.…”
Section: Other Emergent Cvd-associated Skin Diseasesmentioning
confidence: 99%
“…The role of androgens in AGA has been extensively studied. Each HF is developmentally programmed to respond to identically secreted and locally synthesized sex steroid signals in a differential, location-dependent manner (Heilmann-Heimbach et al, 2020Pantelireis and Higgins, 2018;Williams et al, 2020). Whereas AGA has not been specifically examined in the context of TL dynamics, the promoter region of the catalytic subunit of human telomerase, that is, hTERT, contains an estrogen response element, and hTERT transcript levels vary in response to estrogen as well as progesterone exposure in a time-dependent manner (Misiti et al, 2000;Wang et al, 2000).…”
Section: Open Questions In Hf Tl Dynamics and Their Clinical Implicationsmentioning
confidence: 99%
“…Hair restoration is one of the most technologically developed facets of anti-aging [1]. It combines knowledge of hormonal modulation for hair follicle stimulation [2,3], with genetic factors and novel therapeutics including small molecules, peptides transferosomes and exosomes [4][5][6]. Topical formulations, natural products and oral supplements abound as interventions with mixed data on their usage [4].…”
Section: Introductionmentioning
confidence: 99%